х²+10х=39
х²+10х-39=0
k=b/2=10/2=5
D1=k²-ac=5²-1•(-39)=25+39=64
x1=-10-√64/1=-10-8/1=-18/1=-18
x2=-10+√64/1=-10+8/1=-2/1=-2
ответ: -18; -2.
х²+10х=56
х²+10х-56=0
k=b/2=10/2=5
D1=k²-ac=5²-1•(-56)=25+56=81
x1=-5-√81/1=-5-9/1=-14/1=-14
х²=-5+√81/1=-5+9/1=4/1=4
ответ: -14; 4.
(х/3+1)(х/4+1)=20
(х/3+1)(х/4+1)-20=0
(4х+12)(3х+12)-240=0 (привела к общему знаменателю, стала работать с числительным)
12х²+48х+36х+144-240=0
12х²+84х-96=0 |:12
х²+7х-8=0
D=b²-4ac=7²-4•1•(-8)=17
x1=-7-√17/1
x2=-7+√17/1
ответ: -7-√17/1; -7+√17/1.
25/9х²=100
25х²=900 |:25
х²=36
x=±√36
x1=-6; x2=6
ответ: -6; 6.
3х+4=х²
-х²+3х+4=0
х²-3х-4=0
По теореме, обратной теореме Виета:
х1=-1; х2=4
ответ: -1; 4.
1)2((8+x)+x)=20
8+2x=20:2
8+2х=10
2х=10-8
2х=2
х=2:2
х=1-ширина
8+х=8+1=9 - длина
2)2х+х=441
3х=441
х=441:3
х=147-второе число
3х=294-первое число
3)х+у+х-у=140+14
2х=154
х=154:2
х=77-первое число
77+у=140
у=140-77
у=63-второе число
4) х+(х+1)+(х+2)=201
3х+3=201
3х=201-3
3х=198
х= 198:3
х=66
х+1=67
х+2=68
Это числа 66,67 и 68
2) 8x^4y-xy^4=x*y*(8x^3-y^3)=x*y*(2x-y)*(4x+2xy+y)
3) a^3-2a^2-9a+18=a^2*(a-2)-9*(a-2)=(a^2-9)*(a-2)=(a-3)(a+3)(a-2)
4) a^5*b^2+27a^2b^5=a^2*b^2*(a^3+27b^3)=a^2*b^2*(a+3b)*(a^2-3a*b+b^2)